FROM RETRIBUTION TO RESTORATION: INTEGRATING BANKRUPTCY MECHANISMS INTO INDONESIAN CORPORATE CRIMINAL LIABILITY - Ricki Pratama; Yuliati Yuliati; Abdul Madjid (KANUN:JURNAL ILMU HUKUM, 2026)
The ineffectiveness of existing mechanisms for recovering victim losses has been contested in Indonesian criminal law. The New Criminal Code stipulates additional penalties like compensation; however, there is a lack of clear execution guidelines, often resulting in "non-executable" judgments, especially in complex cases with numerous victims. This article addresses the question of how to reconceptualize corporate criminal liability to prioritize the tangible restoration of victim losses through alternative legal instruments. Using a normative juridical method with a conceptual and case-based approach, the study analyses the current legal framework and relevant judicial precedents, such as the First Travel case. The findings reveal that compensation ordered in a final criminal judgment can be legally qualified as a "due and payable debt," thereby fulfilling the requirements of the Bankruptcy and Suspension of Debt Payment Obligation (PKPU) Law (Act 37/2004). By positioning the bankruptcy process as a post-conviction executive mechanism, the state or victims can act as preferred creditors, allowing for the collective and centralized management of corporate assets under court supervision. This study contributes to knowledge lies in the formulation of a victim-oriented corporate criminal liability model that shifts the legal paradigm from a retributive approach to a restorative one. This reconceptualization ensures that corporate liability serves as a functional instrument for ensuring justice through the actual recovery of losses rather than relying on ineffective substitute penalties.